Romanian doctors on the move: The loss of a strategic resource in the context of the COVID-19 pandemic - Raluca Prelipceanu (European Institute of Romania, 2021)
This working paper investigates the migration of Romanian doctors, a worrisome phenomenon, especially due to its long-term effects for the health sector. It draws attention to the fact that, in the context of the COVID-19 pandemic, doctors became a strategic resource for which countries currently compete. The research highlights the main evolutions regarding the doctors' migration from Romania, analysing the period before the accession to European Union (EU) and the post-2007 situation. Equally important for this research are the following categories: native Romanian health specialists, doctors trained in Romanian universities (both the ones that decide to continue working for Romanian hospitals and the ones that leave after their studies/training period). Considering the impact observed for the three groups, we underline the lack of a retention strategy, that could match the needs of the national health sector with the individual professional expectations. Then, we investigate the main reasons for the exodus, based on several interviews conducted with Romanian doctors working in France. We conclude by presenting several measures that Romania aimed to implement to tackle the brain drain of Romanian doctors, and we suggest a series of policy recommendations.
Keywords: 330; workforce migration; Romanian health system; student mobility; retention policy